4M2006 : Second International Conference on Multi-Material Micro Manufacture : 20-22 September 2006, Grenoble, France - International Conference on Multi-Material Micro Manufacture 2006 : Grenoble, France); Menz, W. (Wolfgang); Dimov, S. S., 1959-; Fillon, Bertrand; ScienceDirect eBooks (Oxford ; Boston : Elsevier, 2006)
This work covers the latest state-of-the-art research results from leading European researchers in advanced micro technologies for batch processing of metals, polymers, and ceramics, and the development of new production platforms for micro systems-based products. These contributions are from leading authors at a platform endorsed and funded by the European Union R & D community, as well as leading universities, and independent research and corporate organizations. This comprehensive collection of indexed and peer reviewed articles contains a CD with search functionality. * Contains authoritative papers that reflect the latest developments in micro technologies and micro systems-based products * Includes a user-friendly CD Rom with search functionality.
Keynote Papers -- Major FP6 Projects -- Market Studies on 4M Technologies and Applications -- Components: Fabrication and Assembly Technologies -- Metrology: Inspection and Characterisation Methods -- Novel Materials: Characterisation and Processing -- Process Modelling and Simulation -- Process Characterisation including Process Chains -- Systems: Novel Product and System Designs.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Microtechnology -- Congresses; Microelectromechanical systems -- Congresses; TECHNOLOGY & ENGINEERING -- Electronics -- Digital; TECHNOLOGY & ENGINEERING -- Electronics -- Microelectronics; Microelectromechanical systems; Microtechnology; Electronic books